Family factors of person’s identity development during adolescence and early adulthood - Yablonska, Tetiana (Social Welfare: Interdisciplinary Approach, 2013)
The article is devoted to the study of family factors of personal identity development during adolescence and early adulthood, families with “problem-free” and “deviant” teenagers and high-school students were taken as examples. It was revealed that these categories of children are signifi cantly different in terms of identity development, and their families are essentially different by the parameters of family solidarity and adaptation, by such characteristics of upbringing as positive interest, directive approach, hostility, autonomy, coherence of parents at upbringing.
Keywords: identity; self-identification; family system; solidarity; adaptation; positive interest; directive attitude; hostility; autonomy; inconsistency